Grupo de sala de espera em psico-oncologia na mastologia: estudo das falas das pacientes - Sousa, Adriana Pereira de (2005)
The Waiting Room Group (WRG) is defined as a group modality developed in medical clinics, which is directed to patients and their companions while waiting for the medical consultation (or appointment). The WRG discussed in this research refers to one of the extension projects to the community, carried out by the Hospital de Clínicas da Universidade Federal de Uberlândia (HC-UFU), which composes the professional training period established by the Psycho-Oncology Program in the Mastology of the Psychology Institute in the mentioned hospital. The project attends breast cancer patients and their companions. Breast cancer is among the most frequent sorts of cancer, being considered one of those that have killed women of different ages and social-economic levels the most. However, in spite of the medical evolution, primary prevention is still inaccessible to women affected by this disease. Due to this fact, and also for the increasing number of cases, cancer is considered, today, a public health problem. The goals of this investigation were to identify, analyse, describe and categorise the contents of the reports registered by the trainees in the WRG meetings, as well as knowing and understanding the themes discussed by the patients during the meetings. Such context of data collection allowed us to focus on the project as it has been carried out. The method chosen for this research was the analysis of contents. Registers of five meetings, randomly chosen among an available sample that included reports written from 24/03/2000 to 29/09/2000, were analysed. The conclusion of this stage of the research was determined by the saturation criterion. Ten categories, which were presented according to a decreasing frequency order, arose from the analysis: diagnosis and the treatments for breast cancer; the breast cancer; other resources to deal with breast cancer and its treatments: the support among the WRG participants and religiosity; health versus illness; work related activities; affective relationships; the patient and her participation in the WRG; representation concerning the hospital and the public health system; representations concerning the staff and death. The mentioned categories allowed us to identify the patients representations in relation to the breast cancer; its treatments; the hospital and the medical and psychological staff; the fear of the recurrent cancer and the prevail of death; the use of resources to coping the disease as religiosity, affective relationships and mechanisms to deny the cancer existence. The study of the reports also revealed difficulties related to the reliability of the language presented in the registers, once it combines the vocabulary used by patients and trainees. Another identified problem might be related to the configuration of the reports. The lack of important information about the patients and the companions, who took part in the WRG, impelled us to suggest a different structure for the reports a structure that can be useful for the continuity of the psychological appointments, for the trainees and for researches about this activity. In fact, the WRG consists of an important listening space, where women exchange experiences and are looked after; an essential practice to the preparation of future psychologists.